DETERMINAN MANAJEMEN LABA AKRUAL PADA INDEKS LQ45 DAN JII PERIODE 2010-2015 - Trisnawati, Rina; Mardayaningrum, Mardayaningrum; Khotimah, Laillatul (Riset Akuntansi dan Keuangan Indonesia, 2018)
The purpose of this study is to examine and analyze the mechanisms of corporate governance, leverage and the free cash flow against the accrual earning  management on LQ45 and JII Indexes during the 2010-2015 period. The number of samples in the study is 144 companies in JII index and 121 companies  in JII indexs. Sampling techniques using purposive sampling method. Methods of data analysis using multiple linear regression to test and prove the hypothesis of the study. Research results showed the proxy of corporate governance mechanism with institutional ownership, managerial ownership, the proportion of Board of Commissioners and the audit committee no effect  to accrual earnings management.(prob value >0.05). The free cash flow and leverage have an effect significantly to accrual earning management (prob value <0.05). Meanwhile in JII index, they have the same results. Corporate governance also no effect to accrual earning  management, but the free cash flow and leverage have an effect significantly to accrual earning management. Keywords: corporate governance, leverage, free cash flow, accrual earnings management